Ungoliant, Ella-laraña y la Acromántula: una revisión del mito de Aracné desde lo siniestro - Alonso Valero, Encarnación (Amaltea. Journal of Myth Criticism, 2010)
This paper intends to argue that the Big Spiders that populate the Middle-Earth in The Lord of the Rings and The Silmarillion, by J.R.R. Tolkien (and later, the acromantulas, in the Harry Potter series) are a review of Arachne’s myth from the modern category of the sinister, one of the most important categories in the art and the literature in the 20th century. This category began in the Romanticism and had a theoretical culmination in Freud’s work.